Isolation of ocotillol/ocotillone from Fouquieria splendens (Ocote) using a batch reactor. Issue 5 (2nd May 2022) - Morales-Cepeda, Ana Beatriz; Macclesh del Pino-Pérez, Luis Alejandro; Marmolejo, Mireya; Rivera-Armenta, José Luis; Peraza-Vázquez, Hernan
Abstract: Exploitation of the "ocotillo" tree ( Fouquieria splendens Engelm) to produce ocotillol/ocotillone (o/o) in Northern Mexico hasn't been explored to this date. In the present work, isolation of ocotillol/ocotillone was performed through a batch reactor, which allowed the elimination of alcohol and phenols present in the ocote plant, yielding only resins and waxes from the ocote trunks. The ocotillol/ocotillone was extracted from the remaining resin on the ocote logs by solvent extraction in a batch reactor, to be crystallized after its extraction using a rotary evaporator. FTIR, and NMR analysis exhibited the characteristic ginsenoside bands, while the UV-vis spectrum of ocotillol/ocotillone depicted an absorption band belonging to the O–H bonds, indicating that the group is anchored to the ginsenoside structure and not due to a water signal. Lastly, the thermogravimetric analysis described a common behavior among other ginsenosides. Production of ocotillo/ocotillone has an energy consumption of 3624 kWh/gr. With a cost of 0.478 USD in laboratory equipment, which translates as a plausible sustainable production of ocotillol/ocotillone